Response to a Suspected Toxin-Induced Fish Kill - Ruth Francis-Floyd; Christopher Brooks; Denise Petty (EDIS, 2006)
VM148, a 4-page illustrated fact sheet by Ruth Francis-Floyd, Christopher Brooks, and Denise Petty, describes the proper steps to take in the event of a catastrophic fish kill: samples to take, documentation that will be needed for investigation, and appropriate authorities to notify if a toxic compound is suspected. Published by the UF Department of Veterinary Medicine, November 2006.